PENINGKATAN SUSTAINABILITAS BISNIS KOMUNITAS PELAKU USAHA DI KABUPATEN BANYUMAS - Herwiyanti, Eliada; Hardini, Probo; Wardani, Erna (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The purpose of this community service program is to improve the sustainability of business actors who are members of the Banyumas Raya Business Actors (PUBR) community. The situation analysis of the condition of PUBR as a service partner is experiencing problems in financial management and marketing which have an impact on the instability of income generation. Therefore, the Community Service Team coordinated with PUBR administrators until a solution was agreed upon through the implementation of program socialization, training, and the provision of appropriate technological tools. The community service program has been running effectively since August, the Community Service Team conducted socialization and training related to financial management materials, with the aim that participants understand the importance of good and professional financial management in doing business. Furthermore, in September, the Community Service Team conducted socialization and training related to digital marketing, with the aim that participants understand the importance of marketing with a modern approach through the TikTok application. The financial management training succeeded in improving participants' understanding of financial management. Likewise, the digital marketing training succeeded in improving participants' understanding of the TikTok application. Supported by the assistance of the technological tools provided, PUBR is now more active and enthusiastic in running its business. Thus, the problem-solving method used by the Community Service Team has been effective.